2019
DOI: 10.4067/s0718-221x2019005000201
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and static mechanical properties of Eucalyptus nitens thermally modified in an open and closed reactor system

Abstract: Eucalyptus nitens is a fast growing plantation species that has a good acclimation in Chile. It is commonly used for pulp and paper, but there is a growing market for solid wood products made from this species and an interest on producing high quality material. Thermal modification technology have been used to obtain high quality product out of fast growing plantation species. In this study we modified Eucalyptus nitens to analyse the influences of the process conditions and evaluated its mechanical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
0
11
0
2
Order By: Relevance
“…The catastrophic and brittle failure of the cell wall in dry heat-treated veneers, which was shown by SEM, indicated a rupture of the cellulose chains rather than a failure via interface debonding and pull-out of the fibrils. Dry-HT may have promoted the scission of the cellulose chains, which has been shown previously by the decrease in the degree of polymerization (DP) of cellulose despite an increase in cellulose content [45,46]. A decrease in cellulose DP also occurs during hot water extraction [47,48].…”
Section: Discussionmentioning
confidence: 65%
“…The catastrophic and brittle failure of the cell wall in dry heat-treated veneers, which was shown by SEM, indicated a rupture of the cellulose chains rather than a failure via interface debonding and pull-out of the fibrils. Dry-HT may have promoted the scission of the cellulose chains, which has been shown previously by the decrease in the degree of polymerization (DP) of cellulose despite an increase in cellulose content [45,46]. A decrease in cellulose DP also occurs during hot water extraction [47,48].…”
Section: Discussionmentioning
confidence: 65%
“…1,5 Contrarily, another study asserted that different modification system (open and closed system) does not have a significant bearing on anatomical changes. 13 Scanning electron microscopy observation SEM analyses of untreated and tin-bath treated F. simplex wood are shown in Figures 5-7. The microstructure observation of the untreated samples revealed that the vessels and the cell walls of the wood were intact as well as the visibility of other wood structures ( Figure 5).…”
Section: Transmission Light Microscope Observationmentioning
confidence: 99%
“…Seeking to improve the mechanical properties of this type of timber, Wentzel et al [ 13 , 14 ] studied the feasibility of increasing the physical-mechanical properties of Eucalyptus nitens boards through thermal modification, looking for its application in outdoor exposed decking. Another novel research line has been to the production on structural panels made of Eucalyptus nitens .…”
Section: Introductionmentioning
confidence: 99%